1996
DOI: 10.1042/bj3130473
|View full text |Cite
|
Sign up to set email alerts
|

Human ficolin: cDNA cloning, demonstration of peripheral blood leucocytes as the major site of synthesis and assignment of the gene to chromosome 9

Abstract: Pig ficolins and a number of other proteins contain sequences that are homologous to the C-terminal halves of fibrinogen beta- and gamma-chains. To clone the cDNA for human ficolin, two degenerate oligonucleotide primers were synthesized, based on two stretches of protein sequence that were highly conserved among those proteins, and used for PCR with cDNA from a human uterus lambda gt11 library as a template. A PCR product with a predicted size of 300 bp was obtained and this was used to screen a uterus cDNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(63 citation statements)
references
References 24 publications
(21 reference statements)
2
60
1
Order By: Relevance
“…Two of these (Cys 13 and Cys 18 ) are involved in forming cross-links within a trimer, and Cys 6 mediates association of trimers into multimers of 1-4 trimers (32). MBP-A Cys 6 is thus similar to Cys 24 of ficolin. Only one or two of the three Cys 6 residues per trimer could participate in bonding between trimers.…”
Section: Ficolin Multimerizationmentioning
confidence: 68%
“…Two of these (Cys 13 and Cys 18 ) are involved in forming cross-links within a trimer, and Cys 6 mediates association of trimers into multimers of 1-4 trimers (32). MBP-A Cys 6 is thus similar to Cys 24 of ficolin. Only one or two of the three Cys 6 residues per trimer could participate in bonding between trimers.…”
Section: Ficolin Multimerizationmentioning
confidence: 68%
“…Three types of ficolins have recently been identified in human, L-ficolin/P35 (FCN2 or ficolin 2) (12), M-ficolin (FCN1 or ficolin 1) (13,14), and H-ficolin/Hakata antigen (FCN3 or ficolin 3) (15)(16)(17), and two types of ficolins, ficolins A and B, have been identified in mice (18,19). The fibrinogen-like domain of L-ficolin, forming a globular structure like the CRD of MBL, is the pattern of carbohydrate structures.…”
Section: Introductionmentioning
confidence: 99%
“…The amino acid sequence showed that ficolins consist of a short N-terminal domain, a middle collagen-like domain, and a C-terminal fibrinogen-like (fbg) 1 domain (2,(5)(6)(7). A similar three-domain structure applies to complement protein C1q and the collectins, which include mannose binding protein, conglutinin, and pulmonary surfactant proteins A and D (SP-A and SP-D) (9 -12).…”
mentioning
confidence: 99%